2007
DOI: 10.11606/issn.2176-7262.v40i3p335-344
|View full text |Cite
|
Sign up to set email alerts
|

Trauma, Reabilitação E Qualidade De Vida

Abstract: Este trabalho apresenta uma revisão da literatura, baseada em artigos publicados no período de julho de 2002 a maio de 2007. Procuramos analisar questões referentes a diversos tipos de traumas e suas relações com os programas de reabilitação e qualidade de vida. A revisão foi realizada a partir da consulta às bases de dados internacionais Medline, Scielo e Lilacs e os artigos selecionados foram divididos em quatro categorias, dentro de dois eixos de análise, baseados na Classificação Internacional de Funcional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…Studies suggest that deficits of traumatic origin imply restriction of the pursuit of activities and of social participation, with loss of quality of life. 19 Correlation between DASH and the pain domain of SF-36 suggests that there is a relation between presence of the symptom and the tools. This finding is consistent with the literature found, in which patient with intra-articular fracture of the elbow, submitted to a surgical procedure, were assessed with DASH, SF-36 and other tools.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that deficits of traumatic origin imply restriction of the pursuit of activities and of social participation, with loss of quality of life. 19 Correlation between DASH and the pain domain of SF-36 suggests that there is a relation between presence of the symptom and the tools. This finding is consistent with the literature found, in which patient with intra-articular fracture of the elbow, submitted to a surgical procedure, were assessed with DASH, SF-36 and other tools.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review (30) related to trauma, rehabilitation, and quality of life concluded that people who have disabilities resulting from trauma generally show limitations in activities and social and occupational participation, with impaired quality of life (30). The improvement in a patient's clinical status, whether in relation to body function or structure, contributes to improvement of activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Due to this, nurses are recognized as essential elements in the integration of multidisciplinary rehabilitation teams. This commitment allows to produce knowledge and strategies, and to optimize resources that enable the occurrence of positive transitions (Gomes, et al, 2012;Andrade, et al, 2010;Van Horn, E. R., 2009;De Carlo, M. R. P., et al, 2007). In this perspective, according to the same authors, nursing in the context of the therapeutic process of rehabilitation cannot be understood as individual acts, consisting, instead, in acts of reciprocity, through which the health project is built in partnership, thus contributing decisively to the self-determination of the person, regarding the free and responsible construction of his/her health project.…”
Section: Presentation and Discussionmentioning
confidence: 99%
“…Andrade, et al, 2010;Van Horn, E. R., 2009;De Carlo, M. R. P., et al, 2007). Besides that, the therapeutic relationship promoted by the nurse, characterized by the partnership established with the patient, with respect for his/her capabilities, allows the nurse to understand what is the best moment to intervene, to convey a particular message, and to adjust it, depending on the circumstances.…”
Section: Presentation and Discussionmentioning
confidence: 99%
See 1 more Smart Citation